AN ANALYSIS OF THE HEALTHCARE CENTER SYSTEM AS A GATEKEEPER IN 2018 - Maharanti, Septiana; Oktamiant, Puput i (Journal of Indonesian Health Policy and Administration, 2018)
In managed care, primary healthcarecare facilities acts as the gatekeepers, and its success is judged from the number of visits. In the year 2016, the Healthcare Centers in Tangerang was unable to meet the targets set by BPJS healthcare, ideally the visit rate should reach >150‰ and the referral ratio <10%. However, the visit rate only reachd 41‰ and the referral ratio was 29%. In addition, most healthcare centers the nonspecialised referral ratio was above 5%. The purpose of this research is to analyze the healthcare service system as the gatekeepers in managed care. This research is a descriptive analytical study with a qualitative approach. The data was collected through in-depth interviews, examination of documents and observations. Research conducted at healthcare centers and clinics Pedurenan Pabuaran Tumpeng from May-June 2018. From this research we discovered that the low contact lrate was caused be the low first contact levels, continuity, and comprehensiveness. The registering process was also complicated. We also discovered that the lack of human resources also influences the low contact rate.